PATHOMORPHOLOGY OF CHONDROMATOUS HAMARTOMA DEVELOPED IN LUNG TISSUE - Rakhmanova , Nargizaxon (Medical science of Uzbekistan, 2025)
The aim of the scientific work. Hamartoma is the most common benign tumor of various organs and is considered a benign tumor arising from non-epithelial mesenchymal tissue, the exact cause of which is still not fully understood. Hamartoma consists of cells developing in any tissue and characteristic of this organ. Endobronchial hamartomas occurring in the lung tissue make up 12-20%. It is characterized by a chondromatous and vascular structure in composition and a nodular appearance during microscopic examination. In this study, it was found that hamartoma of the respiratory tract was morphologically manifested in cases of bleeding by the vascular type. Materials and methods. Autopsies, ileum and oral mucosa materials of various forms of myeloblastic leukemia and sepsis were delivered and organized to the center of pathological anatomy of the republic. Of these, 43 male and 26 female materials were received. The prepared pieces are studied morphologically. Results. When analyzing the results of the morphological study, it was noted that the hamartoma, which grew from the large bronchi, was located in the endobronchial tissue structures of the bronchi. It was found that chondromatous changes in the chondromatous tissue of the hamartoma occur in the nodes and bronchial wall of the chondroma and have an atypical structure. It was noted that the cytoplasm of chondrocytes is strongly vacuolated. Among the pieces of chondromatous tissue, the appearance of tubercles and cystic structures among bundles consisting of soft tissues of the bronchial wall was detected. Summary. It was found that 13.4% of chondromatous hamartomas of the respiratory system are located in the wall of large bronchi, 56.2% in the front segments of the lungs, and the rest in the back segments of the lungs (30.2%). It was found that the hamartoma developed in the wall of the large bronchi consists of multifocal and irregularly located chondromatous tissue nodules, and around them, the soft tissues of the bronchial wall and the mucous membrane have grown in a dysregenerative manner. It was observed that in the hamartoma developed from the bronchi within the lung tissue, chondromatous foci appeared both in the wall of the bronchi and in the alveolar tissue.